6 - Impact Pathways of Weather Information for Smallholder Farmers: A Qualitative ex ante Analysis - Yegbemey, Rosaine N.; Aloukoutou, Aline M.; Aïhounton, Ghislain B. D. (Africa Development, 2020)
This article explores ex ante the impact pathways of a hypothetical intervention which consists in providing smallholder farmers with weather-related information. It uses a qualitative approach based on focus group discussions in three villages with smallholder farmers and agricultural extension officers to build a theory of change. Results suggest that providing smallholder farmers with weather-related information has the potential to help them in taking informed production decisions. In doing so, smallholder farmers can better allocate their production resources and eventually record higher yield and income. The ultimate impact is that smallholder farmers will have better lives (i.e. livelihoods). There are several types of weather-related information that can be useful for farmers. There are also several dissemination channels. Some are based on local social networks and others on information and communication technologies. Each channel has strengths and weaknesses and the best or optimal dissemination approach would probably depend on the setting of the intervention area. A number of assumptions need to be in place for an impactful intervention. For instance, weather-related information needs to be accurate, available in a timely manner and easy to use. The described possible impact pathways need to be tested rigorously through policy-oriented research.